Film, form, and culture - Kolker, Robert Phillip 1940-; Gordon, Marsha 1971- (Routledge, Taylor & Francis Group, 2024)
"This fifth edition of Film, Form, and Culture offers a lively introduction to both the formal and cultural aspects of film. With extensive analysis of films past and present, this textbook explores how films and constructed from part to whole. Kolker and Gordon demystify the technical aspects of film making and demonstrate how fiction and non fiction films engage with culture. This new edition includes an expanded examination of digital filmmaking and distribution in the age of streaming, attention to superhero films, an extended chapter on global cinema, new and expanded descriptions of directors and in depth exploration of films. This textbook is an invaluable and exciting resource for students beginning film studies at undergraduate level"--